Threshold-effect of income on periodontitis and interactions with race/ethnicity and education - Roger Keller Celeste; Sara Cioccari Oliveira; Roger Junges (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2019)
ABSTRACT: Objectives: The aims of this study were to explore the shape of the relationship of income and education with periodontal health, and to assess the interactions between them and race/ethnicity. Method: Individual level data from the Brazilian National Oral Health Survey in 2010 (Pesquisa Nacional de Saúde Bucal-SB Brasil 2010) were obtained for 9,779 subjects. Relations between per capita income and education with periodontal health were smoothed using Locally Weighted Scatter-plot Smoother (Lowess) technique. Multivariable logistic regression was used to assess independent effects of income, education, race/ethnicity adjusted for age, sex and time since last dental appointment. Results: Prevalence of adults with moderate to severe and severe periodontitis was 17.6 and 6.5%, respectively. The relationship between periodontal health and income was curvilinear, showing a threshold of no relationship for income levels higher than US$ 600/month. In multivariable analysis, after controlling for covariates, only income was significantly associated with periodontal health. There was no significant interaction of income with race or education, neither between race and education. Conclusion: The relation between periodontal health and income was curvilinear and indicated the presence of a threshold, supporting income transfer programs. Beyond the threshold, only education presented a negative linear relationship with moderate to severe periodontitis.